Proceedings of the 9th ACM International Symposium on Mobile Ad Hoc Networking and Computing 2008
DOI: 10.1145/1374618.1374642
|View full text |Cite
|
Sign up to set email alerts
|

Towards energy efficient VoIP over wireless LANs

Abstract: Wireless LAN (WLAN) radios conserve energy by staying in sleep mode. With real-time applications like VoIP, it is not clear how much energy can be saved by this approach since packets delayed above a threshold are lost. In this work we propose the GreenCall algorithm to derive sleep/wakeup schedules for the WLAN radio to save energy during VoIP calls. The schedules provided by GreenCall consider the energy versus loss-rate tradeoff to ensure application quality is preserved. We implement GreenCall on commodity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The AP in the middle has two clients using VoIP calls. In the simulation, the call deadline for VoIP was set to 250ms [29], i.e., if the VoIP traffic takes more than 250ms to be deliverd at the destination, it is regarded as lost. The simulation results for QoS support through IEEE 802.11e are presented in Table 2.…”
Section: Voice-over-ipmentioning
confidence: 99%
“…The AP in the middle has two clients using VoIP calls. In the simulation, the call deadline for VoIP was set to 250ms [29], i.e., if the VoIP traffic takes more than 250ms to be deliverd at the destination, it is regarded as lost. The simulation results for QoS support through IEEE 802.11e are presented in Table 2.…”
Section: Voice-over-ipmentioning
confidence: 99%
“…Despite the incredible market penetration of smartphones, their utility has been and will remain severely limited by their battery life [6], [8]. A major fraction of the energy consumption in smartphones comes from the wireless network interface controller (WNIC).…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] As a result, the increasing user demands and applications led to the critical requirements of energy consumption and battery life. Among the previous studies, it has been shown that the energy consumption of wireless transmission is a significant part of the overall energy consumption of wireless devices.…”
Section: Introductionmentioning
confidence: 99%